(3bWH GdSQhQ aj hUa GdCfHPI hGdNehQs - (3CMeO Hf GdbGSe GdeYQha HGdQajb GdfOjes
(3ChdgG (B:s
(3Chd GdehLhO efg Hbhd GdTGYQ (B: (3TehS ai YfGf GdeGA JfRh EPG eG QGVgG fRQ GdegGQi s
(3BNQgG (B:s
(3hCJeeJ dg GdMOjK aCeQdi HKeGfjf Cda OQge CQHYjf Yf CNjg hCQHYjf efg Je GdLRA GdChd jJdhg ai GdLRA GdKGfi (B: (3gGQhf GdQTjO s
(3GdhQbI GdCNjQI HNW MOjKs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs